Analysis Of Added Value Of Cape Cotton Oil Refining In Waeapo District, Buru Regency - Leunard Onisivorus Kakisina; Paulus. M. Puttileihalat (Cita konsultindo, 2024)
This research was conducted in Waeapo District, Buru Regency from July to August 2024. The respondents in this study were eucalyptus oil distillation farmers. The analysis used was descriptive analysis and added value analysis (Hayami method). The results of the study showed that clove leaf oil distillation is one type of essential oil that can be produced from the dry clove leaf oil distillation process carried out for 8 hours with an average of 783.33 kg of raw materials used / production. The average added value produced by eucalyptus oil distillation in Waeapo District, Buru Regency is IDR 1,938.92 / kg in one production with an average added value ratio of 44.8%. From the results of this added value analysis, it was obtained that clove leaf oil distillation in Waeapo District, Buru Regency provides high added value ranging from > 40%.